(De)stabilizing Self-Identities in Professional Work - Buch, Anders; Andersen, Vibeke (Nordic Journal of Working Life Studies, 2013)
It is characteristic of much professional work that it is performed in ambiguous contexts. Thus, uncertainty, unpredictability, indeterminacy, and recurrent organizational transformations are an integral part of modern work for, e.g., engineers, lawyers, business consultants, and other professionals. Although key performance indicators and other knowledge management systems are used to set standards of excellence for professionals, the character of professional work is still flexible, open to interpretation and heterarchical. The very successfulness (or unsuccessfulness) of the work is established in a complex work context where various goals, interests, and perspectives are mediated, altered, contested, mangled, and negotiated in a process of sense-making. The work context is heterogeneously populated by various actors (e.g., the customer, the manager, the colleagues) and actants (e.g., quality systems and technical equipment) that give “voice” to (conflicting) interpretations of what constitutes successful work. Thus, the professionals must navigate in a very complex environment where the locus of governance is far from stable. These characteristics of professional work seem to have implications for the way professionals make sense of their work and their own identities. The identity work of professionals is interwoven with their professional training and career background. With an academic training and a professional career, the individual typically identifies with the profession’s values and adopts a certain way of seeing and approaching the world. This professional outlook typically will constitute the basis of the individual’s appraisal of the work and lay out a horizon of expectations in relation to fulfillment, self-realization, and job satisfaction. In this way, the construction of self-identity becomes the yardstick for the individual’s sense-making and, a fortiori, for the individual’s sense of meaningful work. In this paper, we will claim that the ambiguity involved in professional work becomes a potential strain on the identity construction of the employees engaged in professional work and a potential source of enthusiasm and self-fulfillment. On a conceptual basis, the paper develops three interpretative frameworks that are useful in understanding how professionals deal with ambiguity in professional work. To illustrate this point, the paper refers to qualitative material from a research project conducted in six Danish knowledge-intensive firms. Referring to this empirical material, we discuss how professionals perceive and relate to their work and the role played by professionalism in this relation. Drawing on neo-institutional theory our paper discusses how professionals draw on different frameworks of meaning in order to stabilize their identities.